Low Rates of Dual-Site and Concordant Oral-Cervical Human Papillomavirus Infections and Cancers: A Systematic Review - Jordan, Kelsey H.; Beverly Hery, Chloe M.; Zhang, Xiaochen; Paskett, Electra D. (Frontiers in Oncology, 2022)
Objective: The oral-cervical human papillomavirus (HPV) infection/cancer relationship is not well established. Oral-cervical HPV studies were reviewed to assess dual-site occurrence, HPV type concordance, and study quality/deficiencies. Methods: PubMed, EMBASE, Ovid Medline, and Web of Science were searched between 1/1/1990 and 8/10/2021 for studies investigating HPV infections/cancers and type concordance between the oral cavity/oropharynx and cervix. Dual-site and concordant HPV infection rates were summarized as percentages; cancer diagnoses studies were summarized using standardized incidence ratios (SIR). The Quality Assessment Tool for Quantitative Studies (QATQS) evaluated study methodology. Results: One hundred fourteen papers were identified. Most were cross-sectional (n=79, 69%), involved synchronous dual-site HPV testing (n=80, 70%), did not report HPV type concordance (n=62, 54%), and achieved moderate methodological QATQS ratings (n=81, 71%). The overall dual-site infection rate averaged 16%; the HPV type concordance rate averaged 41%, among those dually-infected women. Most HPV-related cancer diagnoses studies reported increased secondary cancer risk, with SIRs generally ranging from 1.4 to 29.4 for secondary cervical cancer after primary oral cancer and from 1.4 to 6.3 for secondary oral cancer after primary cervical cancer. Conclusion/Impact: Oral-cervical HPV infections/cancers remain understudied. Future research should use stronger methodologies and HPV concordance analyses to better understand oral-cervical HPV epidemiology.